2020
DOI: 10.1021/acsabm.0c01100
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry-Controlled Chirality Induced by Co-assembly of Tetraphenylethylene Derivative, γ-CD, and Water-Soluble Pillar[5]arene

Abstract: A stoichiometry-controlled chirality induction was successfully achieved through coassemblies of amphiphilic tetraphenylethylene derivative TPEA, γ-cyclodextrin (γ-CD), and water-soluble pillar[5]arene WP5 in aqueous solution. Stoichiometric variation of WP5 was found to be an effective strategy to induce topological transition between the pseudo[4]rotaxane and the vesicular form. Interestingly, the formation of pseudo[4]rotaxane triggered dual chirality induction from chiral γ-CD to TPEA (negative ICD 1 ), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…46). 378 The tetraphenylethylene unit of TPEA could be encapsulated into the chiral cavity of g-CD through hydrophobic interactions and lead to obvious negative induced circular dichroism (ICD 1 ). During the addition of WP5 (0.05-0.20 equiv.)…”
Section: Construction Of Pseudorotaxanesmentioning
confidence: 99%
“…46). 378 The tetraphenylethylene unit of TPEA could be encapsulated into the chiral cavity of g-CD through hydrophobic interactions and lead to obvious negative induced circular dichroism (ICD 1 ). During the addition of WP5 (0.05-0.20 equiv.)…”
Section: Construction Of Pseudorotaxanesmentioning
confidence: 99%
“…Since the first report of pillararenes and derivatives, , they have been extensively developed in various areas over the past several years. Typically, pillararenes have an interesting and unique planar chirality, which is dynamically reversible between the p R and p S conformations at room temperature. , Interestingly, the planar chirality of pillararenes could be induced and switched by the construction of pseudo[1]­catenanes based on the redox property of the ferrocene moiety or by the addition of an achiral guest or solvents, a metal cation, or an acid/base or controlled by temperature . Additionally, there are some other approaches to induce the planar chirality of pillararenes by forming a chiral (pseudo)­rotaxane, , adding chiral α-amino esters or acids, or forming the regulator-assisted chiral memory of pillararenes with a chiral inducer . Recently, we found that the different planar chiralities of the water-soluble pillar[5]­arene WP5 could be induced by a binding ester moiety or a side-chain moiety of α-amino acids esters in water .…”
mentioning
confidence: 99%
“…Except for using CD as the external stimulus to control the pillar[ n ]arene-based supramolecular self-assembly, pillar[ n ]arene could also be employed to tune the CD-based supramolecular architectures reversibly. 56 For example, abacus-like pseudo[4]rotaxane ( pR -Na + · H1 ) 2 ⊃ G8 ⊂γ-CD (Fig. 3) could be synthesized by using the linear guest molecule—amphiphilic tetraphenylethylene derivative ( G8 , Scheme 3) as the “rod” 75,76 to attract both γ-CD and Na + · H1 as the “wheel” (Scheme 3) in a specialized stoichiometry, i.e.…”
Section: Pillar[n]arene Interacting With CD Via Noncovalent Bondsmentioning
confidence: 99%